Recruitment of the mitotic exit network to yeast centrosomes couples septin displacement to actomyosin constriction - Davide Tamborrini (Nature Portfolio, 2018)
The Mitotic Exit Network (MEN) promotes mitotic exit and cytokinesis but if and how MEN independently controls these two processes is unclear. Here, the authors report that MEN displaces septins from the cell division site to promote actomyosin ring constriction, independently of MEN control of mitotic exit.